Library indexing and abstracting (Anmol Pubications, 2001)
Contents of material: Introduction. Indexing practice. Automatic indexing and abstacting. Bibliographic display. Pre-cordinate indexes. Consistency of indexing. Periodicals listing. Online computer service. Abstracs: Types and functions. Bibliographic control. Books. Acquisition systems. Indexing and abstracting in information age.